2018
DOI: 10.1152/japplphysiol.00713.2017
|View full text |Cite
|
Sign up to set email alerts
|

Chronic exposure to electronic cigarettes results in impaired cardiovascular function in mice

Abstract: Proponents for electronic cigarettes (E-cigs) claim that they are a safe alternative to tobacco-based cigarettes; however, little is known about the long-term effects of exposure to E-cig vapor on vascular function. The purpose of this study was to determine the cardiovascular consequences of chronic E-cig exposure. Female mice (C57BL/6 background strain) were randomly assigned to chronic daily exposure to E-cig vapor, standard (3R4F reference) cigarette smoke, or filtered air ( n = 15/group). Respective whole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
125
4
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(137 citation statements)
references
References 69 publications
7
125
4
1
Order By: Relevance
“…Further support for the validity and the clinical applicability of our animal model derives from literature documenting that mouse studies do ā€œmapā€ very well to humans in the context of tobacco exposure 14, 75, 76. In fact, given the challenges in human studies and the difficulty in drawing conclusions due to the variability in the device and eā€liquid products, usersā€™ experience, and concomitant exposure to other forms of tobacco, the current model gives us great flexibility in mimicking many aspects of human exposure.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Further support for the validity and the clinical applicability of our animal model derives from literature documenting that mouse studies do ā€œmapā€ very well to humans in the context of tobacco exposure 14, 75, 76. In fact, given the challenges in human studies and the difficulty in drawing conclusions due to the variability in the device and eā€liquid products, usersā€™ experience, and concomitant exposure to other forms of tobacco, the current model gives us great flexibility in mimicking many aspects of human exposure.…”
Section: Discussionmentioning
confidence: 92%
“…Furthermore, a case of acute myocardial infarction in a young man was recently reported after only 1Ā month of eā€cigarette use 90. Separate studies showed that eā€cigarettes also induce myocardial DNA damage,91 arterial stiffness14 and stroke92 in mice. While the current data indicate that shortā€term exposure to eā€cigarettes is associated with cardiovascular harm, one can speculate that longer use/exposure to eā€cigarette would have even more detrimental effects; this will be the scope of future investigations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21,22 Both the solvent and the battery output voltage significantly affect levels of carbonyl compounds found in the aerosol. These compounds have been implicated in the development of oxidative stress and release of inflammatory mediators, 23,24 increasing cardiovascular risk [25][26][27] and platelet function alteration, 28 airway epithelial injury, and creating disturbances in gas exchange function. 29 Furthermore, repeated exposure of the heating element to high temperatures allows emission of nanoparticles 30 with a potential harmful effect on the respiratory system.…”
mentioning
confidence: 99%
“…This resulted in a 2.5-fold increase in aortic stiffness, a 24% lower maximal aortic relaxation in response to methacholine and a trend towards a reduction in left ventricular ejection fraction 97. Nonetheless, in humans, it seems that electronic cigarettes could be less harmful than standard cigarettes, as hypertensive patients who switched to electronic cigarettes benefited from a reduction in mean arterial blood pressure and improved pressure control 98. It should be emphasised that most of the data on the cardiovasculareffects of electronic cigarettes are derived from preclinical, crosssectional or small-sized clinical studies in which standard cigarettes were used as a comparison arm, thus providing limiting and conflicting results.…”
mentioning
confidence: 99%